Metastatic Melanoma in Sentinel Node-Negative Patients: The Ottawa Experience - Ward, Chloe E; MacIsaac, Jennifer L; Heughan, Caroline E; Weatherhead, Louis (Journal of cutaneous medicine and surgery, 2018)
Lymph node involvement is a major independent prognostic factor for survival in patients with malignant melanoma. Sentinel lymph node biopsy (SLNB) detection of microscopic nodal melanoma has been shown to improve both 5-year survival and 5-year disease-free survival. To determine the rate of metastatic melanoma in SLNB-negative patients at long-term follow-up. Study subjects include all 152 patients who had a negative SLNB and were followed at the Ottawa Regional Cancer Centre (ORCC) between 1999 and 2004. Patients with a follow-up period less than 6 months, more than 1 primary melanoma, and metastatic melanoma at diagnosis were excluded. Age at diagnosis, sex, Breslow thickness, ulceration, mitoses, regression, Clark level, anatomical location, development of metastatic melanoma, time to detection of metastatic disease, and time to death from melanoma were studied. In this retrospective study at the ORCC, 40 of 140 (28.6%) patients with a single primary melanoma developed metastatic melanoma following negative SLNB at a mean follow-up of 63 months. The rate of metastatic melanoma following negative SLNB at long-term follow-up at the ORCC is higher than the upper limit of rates reported in the literature (6%-24%). The reason for this is multifactorial, and the long follow-up period of 5 years allowed for detection of metastatic disease at a mean of 3.9 years. Long-term prognosis may be guarded in node-negative patients with a primary cutaneous melanoma, and surveillance by a multidisciplinary team is crucial.